PRE-PARTICIPATION HEALTH QUESTIONNAIRE IN MAJOR ATHLETIC CHAMPIONSHIPS: FEASIBILITY AND INTEREST TO DETERMINE INJURY AND ILLNESS RISK FACTORS. Issue 7 (11th March 2014) - Edouard, P; Branco, P; Jacobsson, J; Timpka, T; Kowalski, J; Nilsson, S; Karlsson, D; Depiesse, F; Alonso, JM
Abstract : Background: The current injury and illness (I&I) surveillance system in association to athletics championships have to be improved by collecting pre-participation data for risk factors analyses. Objectives: To evaluate a pre-participation health questionnaire (PHQ) for collecting health status data from athletes for risk factors analyses and to describe incidence and characteristics of I&I occurred during a major indoor Athletics championships. Design: Cohort study using retrospective athlete self-report data on health status for the 4 weeks prior to the championship and prospective recording of in-championship injuries and illnesses. Setting: 32 st European Athletics Indoor Championships 2013 in Göteborg, Sweden. Participants: A sub-cohort of athletes (n=127) for PHQ study and 577 registered athletes for I&I study. Risk factor assessment: Age, gender, pre-competition pain, pre-competition injury, pre-competition illness, pre-competition training load and fatigue. Main outcome measures: Newly incurred injury and illness at the championships. Results: In the I&I study, 60 injuries (104.6/1000 registered athletes) were recorded. The most common injury cause was "field play conditions" (31%), followed by overuse (29%). 29 illnesses were reported (12.6 illnesses per 1000 athlete days), with upper respiratory tract infection and gastro-enteritis/diarrhoea as the most common diagnoses. 74 athletes submitted a complete PHQ (58.3%). An univariate statistical analysis showed that athletes having trained more than 12 hours per week were at increased risk for suffering a new injury (Relative risk (RR)=4.9 (95% Confidence interval (95% CI):1.2–20.7)), and athletes who presented a pre-participation health problem were more likely to suffer a new illness (RR=2.7; (95% CI:1.1–6.7)). Conclusions: An athlete self-report PHQ was feasible and allowed for pre-participation screening of individuals at risk. Injury risk during indoor championships seems slightly lower than during outdoor championships with specific injury types that can be attributed to the indoor track conditions.